Improved Information Literacy of Elementary School Students About Living Pharmacies Through Information and Communication Media (ICT) - Oky Dwiana; M. Muktiarni; Jonah Mupita (ASEAN Journal of Science and Engineering Education, 2022)
The availability of family medicinal plants as living pharmacies has been widely used by the community. The increasing use of herbal medicines causes scientific information related to these medicines to have an important position for the public. Ideally, all scientific information in the form of electronic files can be obtained from the internet. However, this condition cannot be fulfilled because of the high cost of internet subscription. Therefore, the knowledge that develops in the community about medicines needs to be documented as well as possible so that it can be maintained and studied by the next generation. This study aims to improve students' literacy skills about living pharmacies through information and communication media for elementary school students in the 2021/2022 academic year. We was conducted using a qualitative descriptive method accompanied by library research activities. This was proven through a pre-test questionnaire at the beginning and the average result of 17 students was 70.65%. After students were given material in the form of reading material about living pharmacies, students' understanding increased by 13.42%. Based on these data, it was revealed that most of the respondents had good knowledge after being given a literature study about living pharmacies.